Method for preparing copper-chromium-niobium series materials based on SLM
By using powder bins with different Cr and Nb contents in the SLM process, combining vacuum drying and ultrasonic vibration treatment, the problems of complex SLM process and low material utilization are solved, and the high accuracy of copper chromium niobium alloy materials are achieved and low-cost production, suitable for the manufacturing of complex parts.
Patent Information
- Application Number
- CN202411649591.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing SLM process is complex and has low material utilization when preparing copper-chromium-niobium alloy materials, making it difficult to achieve high accuracy and low cost production of composite materials, especially when manufacturing complex parts.
Using a single SLM device, the copper-chromium-niobium alloy powder is printed layer by layer by layer by layer by replacement of powder bins with different Cr and Nb contents, and the additive manufacturing of functional gradient materials is realized. Combined with vacuum drying, ultrasonic vibration and screening treatment, Cr and The copper-chromium-niobium material with a gradually increasing Nb content reduces surface roughness and improves accuracy.
Gradient printing of copper chromium niobium series materials has been realized, which improves material utilization and production accuracy, reduces equipment costs, is suitable for manufacturing parts with complex geometric shapes and internal structures, and can integrate multiple functions in the same component. Meet different application needs.
Smart Images

Figure CN119144864A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of copper-chromium-niobium alloys, and in particular to a method for preparing copper-chromium-niobium series materials based on SLM. Background Art
[0002] Copper-chromium-niobium alloy is widely used in high-temperature service environments such as liquid rocket engines and thermonuclear reactors due to its excellent high-temperature mechanical properties and conductivity. The SLM process is a technology that uses a layer-by-layer printing method to manufacture solid parts. In recent years, the prior art has successfully used SLM to realize the development of GRCop-84 and GRCop-42 alloy combustion chambers, and the material properties produced by the SLM process are comparable to those of the traditional extrusion process. The advantages of this process include the manufacture of complex internal cooling channels and reduced manufacturing time. However, the characteristics of the SLM process itself require that the process is limited to a single component material. Therefore, for the preparation of composite samples, most current studies use methods combined with other forming methods, such as cold spraying, directed energy deposition, etc. The overall process is relatively complicated, and for parts with higher complexity, cold spraying and directed energy deposition techniques cannot achieve the ideal accuracy requirements. They often need to enlarge the size and remove excess material through machining, which will cause material waste and high process costs. Based on this, the present application proposes a method for preparing copper-chromium-niobium series materials based on SLM. Summary of the invention
[0003] The main purpose of this application is to provide a method for preparing copper-chromium-niobium series materials based on SLM, aiming to solve the technical problems of complex SLM preparation process and low material utilization rate of existing copper-chromium-niobium materials.
[0004] To achieve the above objectives, the present application proposes a method for preparing copper-chromium-niobium series materials based on SLM, comprising the following steps: S1. Pre-treating a plurality of copper-chromium-niobium alloy powders respectively to obtain pre-treated copper-chromium-niobium series alloy powders; S2. Establish a three-dimensional solid model of the sample to be formed and import it into the SLM printer, set the printing parameters, respectively load the pre-treated copper-chromium-niobium series alloy powder into each powder bin of the SLM printer, evacuate and introduce protective gas, and then print the first copper-chromium-niobium material layer by layer until the nth layer; S3, replacing the powder bin, and printing the second copper-chromium-niobium material layer by layer starting from the n+1 layer according to the printing parameters to the required thickness; S4, repeat step S3 until the printing of various copper, chromium and niobium materials is completed to obtain a molded sample; The contents of Cr and Nb in each of the copper-chromium-niobium materials are different.
[0005] Optionally, the copper-chromium-niobium alloy powders may include the following components by mass percentage: Cr: 0.8%-7%, Nb: 0.35%-4%, Fe≤0.005%, O≤0.05%, Si≤0.05%, Al≤0.05%, and the balance is Cu.
[0006] Optionally, in the plurality of copper-chromium-niobium alloy powders, the mass ratio of Cr to Nb is 1.14:1.
[0007] Optionally, in step S3 and step S4, each time the next copper-chromium-niobium material is printed, the content gradient of Cr and Nb in the replaced powder bin increases.
[0008] Optionally, the step of pretreating the plurality of copper-chromium-niobium alloy powders respectively to obtain pretreated copper-chromium-niobium series alloy powders comprises: A variety of copper-chromium-niobium alloy powders were vacuum dried, cooled in the furnace, and then subjected to ultrasonic vibration treatment. After sieving through a 270-mesh sieve, the sieved material was taken to obtain pre-treated copper-chromium-niobium series alloy powders.
[0009] Optionally, in the step of vacuum drying, the drying temperature is 100°C-120°C, the drying time is 4h-10h, and the vacuum degree is 1×10 -4 Pa-1×10 -3 Pa.
[0010] Optionally, in the step of performing ultrasonic vibration treatment, the ultrasonic vibration frequency is 35kHz-40kHz, the ultrasonic vibration deviation angle is 8°-10°, and the ultrasonic vibration treatment time is 5min-10min.
[0011] Optionally, the printing parameters include: The scanning speed is 400mm / s-1600mm / s, the scanning spacing is 0.05mm-0.12mm, the printing power is 370W-460W, and the printing single layer thickness is 0.02mm-0.08mm.
[0012] Optionally, in the step of evacuating the vacuum and introducing the protective gas, the vacuum is evacuated to a vacuum degree of 3Pa-5Pa, and the protective gas is argon.
[0013] Optionally, after step S4, the method further includes: Performing surface treatment on the molded sample to reduce surface roughness; The surface treatment method includes one or more of liquid sandblasting, abrasive flow machining, electrolytic polishing and chemical reagent cleaning.
[0014] This application includes at least the following beneficial effects: The preparation method of the present application only requires a single SLM device. By replacing the powder bin containing different Cr and Nb contents, a variety of copper-chromium-niobium alloy powders can be provided in one construction operation, realizing the additive manufacturing of functionally gradient copper-chromium-niobium series materials. Compared with the SLM used in the prior art for the molding of composite materials, In combination with the directional deposition process, after a single material semi-finished product is formed by SLM, another part is prepared layer by layer on the semi-finished product using directional deposition, and then the excess part is removed by surface machining to obtain the required bimetallic sample. The present application only needs to use the SLM process, and in one construction operation, by setting the copper-chromium-niobium alloy powder with gradually increasing Cr and Nb contents to print layer by layer, and print the copper-chromium-niobium material with gradually increasing Cr and Nb contents, thereby realizing the gradient printing of the copper-chromium-niobium series of materials, and according to specific application requirements, through the reasonable combination of different copper-chromium-niobium materials, the composition and structure of the copper-chromium-niobium materials in different regions are controlled, multiple functions can be integrated in one component, or a smooth transition of performance can be achieved in the same component, and a composite material with multiple properties such as plasticity and strength can be prepared, which has high precision and is conducive to the preparation of parts with complex geometric shapes and internal structures, and has the characteristics of low equipment cost, easy development and high material utilization, and copper-chromium-niobium powders with different chromium and niobium contents do not need to be screened, and can be directly recycled or applied to other products, which can meet different application requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. It is obvious that the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.
[0016] Figure 1 This is a flow chart of the method for preparing copper-chromium-niobium series materials based on SLM described in an embodiment of the present application.
[0017] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0018] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0019] In view of the technical problems existing in the prior art, the embodiments of the present application provide a method for preparing copper-chromium-niobium series materials based on SLM, such as Figure 1 As shown, the following steps are included: S1. Pre-treating a plurality of copper-chromium-niobium alloy powders respectively to obtain pre-treated copper-chromium-niobium series alloy powders.
[0020] In the specific implementation process, the pretreatment method is: vacuum drying the various copper-chromium-niobium alloy powders respectively, cooling them in the furnace, and then subjecting them to ultrasonic vibration treatment, and then sieving them through a 270-mesh sieve, taking the sieve under the sieve to obtain pretreated copper-chromium-niobium series alloy powders.
[0021] Specifically, in the step of vacuum drying, the drying temperature is 100°C-120°C, the drying time is 4h-10h, and the vacuum degree is 1×10 -4 Pa-1×10 -3 Pa.
[0022] Specifically, in the step of performing ultrasonic vibration treatment, the ultrasonic vibration frequency is 35kHz-40kHz, the ultrasonic vibration deviation angle is 8°-10°, and the ultrasonic vibration treatment time is 5min-10min.
[0023] In the specific implementation process, various copper-chromium-niobium alloy powders include the following components by mass percentage: Cr: 0.8%-7%, Nb: 0.35%-4%, Fe≤0.005%, O≤0.05%, Si≤0.05%, Al≤0.05%, and the balance is Cu.
[0024] Specifically, in the various copper-chromium-niobium alloy powders, the mass ratio of Cr to Nb is 1.14:1.
[0025] S2. A three-dimensional solid model of the sample to be formed with scanning path information of each layer is established and imported into the SLM printer. The printing parameters are set at the same time. The three-dimensional solid model is layered using a cutting software to form a laser processing scanning path for each layer. The pretreated copper-chromium-niobium series alloy powders are respectively loaded into each powder bin of the SLM printer. After the base plate is placed, a scraper is installed, vacuuming is performed, and argon gas is introduced as a protective gas, and the first copper-chromium-niobium material is printed layer by layer until the nth layer.
[0026] The value range of n is ≥2.
[0027] In the specific implementation process, the printing parameters include: The scanning speed is 400mm / s-1600mm / s, the scanning spacing is 0.05mm-0.12mm, the printing power is 370W-460W, and the printing single layer thickness is 0.02mm-0.08mm.
[0028] In the specific implementation process, when evacuating, the vacuum degree is 3Pa-5Pa, and the protective gas is argon.
[0029] S3, replacing the powder bin, and printing the second copper-chromium-niobium material layer by layer starting from the n+1 layer according to the printing parameters to the required thickness.
[0030] S4. Repeat step S3 until the printing of various copper-chromium-niobium materials is completed to obtain a molded sample.
[0031] In the specific implementation process, the present application can customize the characteristics of the material according to the needs, control the printing of various copper-chromium-niobium materials and regulate the Cr and Nb content in the copper-chromium-niobium materials in different regions, so as to meet different application requirements. For example, in aerospace applications, complex parts with both high-temperature oxidation resistance and high strength can be manufactured to meet the needs of extreme working environments; the stress concentration problem caused by performance differences in different regions of traditional copper-chromium-niobium materials can also be effectively reduced through the smooth transition of Cr and Nb content, thereby improving the fatigue life and fracture resistance of parts.
[0032] S5, performing surface treatment on the molded sample to reduce surface roughness; The surface treatment method includes one or more of liquid sandblasting, abrasive flow machining, electrolytic polishing and chemical reagent cleaning.
[0033] In the specific implementation process, the content of Cr and Nb in each copper-chromium-niobium material is different. When printing each next copper-chromium-niobium material, the content of Cr and Nb in the replaced powder bin increases gradually, but the mass ratio of Cr to Nb is 1.14:1.
[0034] The preparation method of the present application only requires a single SLM device. By replacing the powder bin containing different Cr and Nb contents, a variety of copper-chromium-niobium alloy powders can be provided in one construction operation, realizing the additive manufacturing of functionally gradient copper-chromium-niobium series materials. Compared with the SLM used in the prior art for the molding of composite materials, In combination with the directional deposition process, after a single material semi-finished product is formed by SLM, another part is prepared layer by layer on the semi-finished product using directional deposition, and then the excess part is removed by surface machining to obtain the required bimetallic sample. The present application only needs to use the SLM process, and in one construction operation, by setting the copper-chromium-niobium alloy powder with gradually increasing Cr and Nb contents to print layer by layer, and print the copper-chromium-niobium material with gradually increasing Cr and Nb contents, thereby realizing the gradient printing of the copper-chromium-niobium series of materials, and according to specific application requirements, through the reasonable combination of different copper-chromium-niobium materials, the composition and structure of the copper-chromium-niobium materials in different regions are controlled, multiple functions can be integrated in one component, or a smooth transition of performance can be achieved in the same component, and a composite material with multiple properties such as plasticity and strength can be prepared, which has high precision and is conducive to the preparation of parts with complex geometric shapes and internal structures, and has the characteristics of low equipment cost, easy development and high material utilization, and copper-chromium-niobium powders with different chromium and niobium contents do not need to be screened, and can be directly recycled or applied to other products, which can meet different application requirements.
[0035] Specifically, functional gradient materials refer to composite materials with special functions whose chemical composition, microstructure, porosity and other elements change continuously or quasi-continuously from one side to the other along the thickness or length of the material, so that its physical, chemical and other properties change continuously and gradiently according to the design requirements. Due to the spatial gradient of its composition and the material property gradient induced by the microstructure, it is more suitable for high-performance multifunctional applications, and the multifunctional state of the component can be customized to meet the expected performance requirements. This application successfully achieved the preparation of functional gradient copper-chromium-niobium materials by adjusting the Cr and Nb contents to gradually increase.
[0036] The above technical solution of the present application is described in detail below in conjunction with specific embodiments.
[0037] Example 1 A method for preparing copper-chromium-niobium series materials based on SLM, comprising the following steps; S1. Prepare the first copper-chromium-niobium alloy powder according to the ratio of Cr: 0.8%, Nb: 0.7%, Fe: 0.003%, O≤0.05%, Si: 0.04%, Al: 0.04%, and Cu as the balance, and keep the mass ratio of Cr to Nb at about 1.14:1; On the basis of the first copper-chromium-niobium alloy powder, the content of Cr is increased to 1.6%, the content of Nb is increased to 1.4%, and the contents of other components remain unchanged, thereby obtaining a second copper-chromium-niobium alloy powder; On the basis of the second copper-chromium-niobium alloy powder, the content of Cr is increased to 2.4% and the content of Nb is increased to 2.1%, and the contents of other components remain unchanged, thereby obtaining a third copper-chromium-niobium alloy powder; On the basis of the third copper-chromium-niobium alloy powder, the content of Cr is increased to 3.2% and the content of Nb is increased to 2.8%, and the contents of other components remain unchanged, thereby obtaining a fourth copper-chromium-niobium alloy powder; On the basis of the fourth copper-chromium-niobium alloy powder, the content of Cr is increased to 4.8%, the content of Nb is increased to 4.2%, and the contents of other components remain unchanged, thereby obtaining a fifth copper-chromium-niobium alloy powder; On the basis of the fifth copper-chromium-niobium alloy powder, the content of Cr is increased to 6.2% and the content of Nb is increased to 5.4%, and the contents of other components remain unchanged, thereby obtaining a sixth copper-chromium-niobium alloy powder; The various copper-chromium-niobium alloy powders were vacuum dried at 110 °C, 7 h, and a vacuum degree of 1.5 × 10 -3 Pa, after cooling in the furnace, ultrasonic vibration treatment is performed, the ultrasonic vibration frequency is 37kHz, the ultrasonic vibration deviation angle is 9°, the ultrasonic vibration treatment time is 7min, and then sieved through a 270-mesh sieve, and the sieve underflow is taken to obtain a pretreated copper-chromium-niobium series alloy powder; S2. Establish a three-dimensional solid model of the sample to be formed with the scanning path information of each layer and import it into the SLM printer, set the printing parameters at the same time, and use the cutting software to layer the three-dimensional solid model to form the laser processing scanning path of each layer; respectively fill the pre-treated copper-chromium-niobium series alloy powders into the powder bin of the SLM printer, place the bottom plate, install a scraper, evacuate to a vacuum degree of 4Pa, and introduce argon as a protective gas, use the powder bin filled with the first copper-chromium-niobium alloy powder and use the scraper to evenly spread the first copper-chromium-niobium alloy powder to the laser processing area, and print layer by layer until the nth layer to obtain the first copper-chromium-niobium material; The printing parameters are set as follows: The scanning speed is 1000mm / s, the scanning interval is 0.08mm, the printing power is 390W, and the printing single layer thickness is 0.03mm; S3, replacing the powder bin filled with the first copper-chromium-niobium alloy powder with the powder bin filled with the second copper-chromium-niobium alloy powder, and printing the second copper-chromium-niobium material layer by layer starting from the n+1 layer according to the above printing parameters to the required thickness; S4. Repeat step S3 until the printing of six copper-chromium-niobium materials is completed, and then perform liquid sand blasting to reduce the surface roughness to obtain a molded sample.
[0038] Example 2 A method for preparing copper-chromium-niobium series materials based on SLM, comprising the following steps; S1. Prepare the first copper-chromium-niobium alloy powder according to the ratio of Cr: 0.8%, Nb: 0.7%, Fe: 0.003%, O≤0.05%, Si: 0.04%, Al: 0.04%, and Cu as the balance, and keep the mass ratio of Cr to Nb at about 1.14:1; On the basis of the first copper-chromium-niobium alloy powder, the content of Cr is increased to 3.2%, the content of Nb is increased to 2.8%, and the contents of other components remain unchanged, thereby obtaining a second copper-chromium-niobium alloy powder; On the basis of the second copper-chromium-niobium alloy powder, the content of Cr is increased to 6.2% and the content of Nb is increased to 5.4%, and the contents of other components remain unchanged, thereby obtaining a third copper-chromium-niobium alloy powder; The various copper-chromium-niobium alloy powders were vacuum dried at 100 °C, 10 h, and a vacuum degree of 1×10 -3 Pa, after cooling in the furnace, ultrasonic vibration treatment is performed, the ultrasonic vibration frequency is 35kHz, the ultrasonic vibration deviation angle is 8°, the ultrasonic vibration treatment time is 10min, and then sieving is performed through a 270-mesh sieve, and the sieve underflow is taken to obtain a pretreated copper-chromium-niobium series alloy powder; S2. Establish a three-dimensional solid model of the sample to be formed with the scanning path information of each layer and import it into the SLM printer, set the printing parameters at the same time, and use the cutting software to layer the three-dimensional solid model to form the laser processing scanning path of each layer; respectively fill the pre-treated copper-chromium-niobium series alloy powders into the powder bin of the SLM printer, place the bottom plate, install a scraper, evacuate to a vacuum degree of 3Pa, and introduce argon as a protective gas, use the powder bin filled with the first copper-chromium-niobium alloy powder and use the scraper to evenly spread the first copper-chromium-niobium alloy powder to the laser processing area, and print layer by layer until the nth layer to obtain the first copper-chromium-niobium material; The printing parameters are set as follows: The scanning speed is 800mm / s, the scanning interval is 0.08mm, the printing power is 370W, and the printing single layer thickness is 0.04mm; S3, replacing the powder bin filled with the first copper-chromium-niobium alloy powder with the powder bin filled with the second copper-chromium-niobium alloy powder, and printing the second copper-chromium-niobium material layer by layer starting from the n+1 layer according to the above printing parameters to the required thickness; S4. Repeat step S3 until the printing of the three copper, chromium and niobium materials is completed, and then perform abrasive flow machining to reduce the surface roughness to obtain a molded sample.
[0039] Example 3 A method for preparing copper-chromium-niobium series materials based on SLM, comprising the following steps; S1. Prepare the first copper-chromium-niobium alloy powder according to the ratio of Cr: 0.8%, Nb: 0.7%, Fe: 0.003%, O≤0.05%, Si: 0.04%, Al: 0.04%, and Cu as the balance, and keep the mass ratio of Cr to Nb at about 1.14:1; On the basis of the first copper-chromium-niobium alloy powder, the content of Cr is increased to 1.6%, the content of Nb is increased to 1.4%, and the contents of other components remain unchanged, thereby obtaining a second copper-chromium-niobium alloy powder; On the basis of the second copper-chromium-niobium alloy powder, the content of Cr is increased to 3.2% and the content of Nb is increased to 2.8%, and the contents of other components remain unchanged, thereby obtaining a third copper-chromium-niobium alloy powder; On the basis of the third copper-chromium-niobium alloy powder, the content of Cr is increased to 6.2% and the content of Nb is increased to 5.4%, and the contents of other components remain unchanged, thereby obtaining a fourth copper-chromium-niobium alloy powder; The various copper-chromium-niobium alloy powders were vacuum dried at 120 °C, 4 h, and a vacuum degree of 1×10 -4 Pa, after cooling in the furnace, ultrasonic vibration treatment is performed, the ultrasonic vibration frequency is 40kHz, the ultrasonic vibration deviation angle is 10°, the ultrasonic vibration treatment time is 5min, and then sieved through a 270-mesh sieve, and the sieve underflow is taken to obtain a pretreated copper-chromium-niobium series alloy powder; S2. Establish a three-dimensional solid model of the sample to be formed with the scanning path information of each layer and import it into the SLM printer, set the printing parameters at the same time, and use the cutting software to layer the three-dimensional solid model to form the laser processing scanning path of each layer; respectively fill the pre-treated copper-chromium-niobium series alloy powders into the powder bin of the SLM printer, place the bottom plate, install a scraper, evacuate to a vacuum degree of 5Pa, and introduce argon as a protective gas, use the powder bin filled with the first copper-chromium-niobium alloy powder and use the scraper to evenly spread the first copper-chromium-niobium alloy powder to the laser processing area, and print layer by layer until the nth layer to obtain the first copper-chromium-niobium material; The printing parameters are set as follows: The scanning speed is 1000mm / s, the scanning interval is 0.12mm, the printing power is 460W, and the printing single layer thickness is 0.04mm; S3, replacing the powder bin filled with the first copper-chromium-niobium alloy powder with the powder bin filled with the second copper-chromium-niobium alloy powder, and printing the second copper-chromium-niobium material layer by layer starting from the n+1 layer according to the above printing parameters to the required thickness; S4. Repeat step S3 until the printing of the four copper, chromium and niobium materials is completed, and then perform electrolytic polishing to reduce the surface roughness to obtain a molded sample.
[0040] Example 4 A method for preparing copper-chromium-niobium series materials based on SLM, comprising the following steps; S1. Prepare the first copper-chromium-niobium alloy powder according to the ratio of Cr: 0.8%, Nb: 0.7%, Fe: 0.003%, O≤0.05%, Si: 0.04%, Al: 0.04%, and Cu as the balance, and keep the mass ratio of Cr to Nb at about 1.14:1; On the basis of the first copper-chromium-niobium alloy powder, the content of Cr is increased to 2.4%, the content of Nb is increased to 2.1%, and the contents of other components remain unchanged, thereby obtaining a second copper-chromium-niobium alloy powder; On the basis of the second copper-chromium-niobium alloy powder, the content of Cr is increased to 4.8%, the content of Nb is increased to 4.2%, and the contents of other components remain unchanged, thereby obtaining a third copper-chromium-niobium alloy powder; On the basis of the third copper-chromium-niobium alloy powder, the content of Cr is increased to 6.2% and the content of Nb is increased to 5.4%, and the contents of other components remain unchanged, thereby obtaining a fourth copper-chromium-niobium alloy powder; The various copper-chromium-niobium alloy powders were vacuum dried at a temperature of 105 °C, a drying time of 5 h, and a vacuum degree of 1×10 -4 Pa, after cooling in the furnace, ultrasonic vibration treatment is performed, the ultrasonic vibration frequency is 38kHz, the ultrasonic vibration deviation angle is 8°, the ultrasonic vibration treatment time is 6min, and then sieved through a 270-mesh sieve, and the sieve underflow is taken to obtain a pretreated copper-chromium-niobium series alloy powder; S2. Establish a three-dimensional solid model of the sample to be formed with the scanning path information of each layer and import it into the SLM printer, set the printing parameters at the same time, and use the cutting software to layer the three-dimensional solid model to form the laser processing scanning path of each layer; respectively fill the pre-treated copper-chromium-niobium series alloy powders into the powder bin of the SLM printer, place the bottom plate, install a scraper, evacuate to a vacuum degree of 4Pa, and introduce argon as a protective gas, use the powder bin filled with the first copper-chromium-niobium alloy powder and use the scraper to evenly spread the first copper-chromium-niobium alloy powder to the laser processing area, and print layer by layer until the nth layer to obtain the first copper-chromium-niobium material; Among them, the printing parameters are set as follows: The scanning speed is 800mm / s, the scanning interval is 0.07mm, the printing power is 380W, and the printing single layer thickness is 0.05mm; S3, replacing the powder bin filled with the first copper-chromium-niobium alloy powder with the powder bin filled with the second copper-chromium-niobium alloy powder, and printing the second copper-chromium-niobium material layer by layer starting from the n+1 layer according to the above printing parameters to the required thickness; S4. Repeat step S3 until the printing of the four copper-chromium-niobium materials is completed, and then clean them with chemical reagents to reduce the surface roughness to obtain a molded sample.
[0041] Experimental example The samples obtained in Examples 1-4 were subjected to hot isostatic pressing, and then the thermal conductivity and strength were tested respectively. 0.8 Nb 0.7 and CuCr 6.2 Nb 5.4 As a control group, the test results are shown in Table 1 below.
[0042] Table 1
[0043] As can be seen from Table 1, CuCr 0.8 Nb 0.7 Although the sample has a high thermal conductivity, its strength is low, and CuCr 6.2 Nb 5.4 Although the sample has high strength, its thermal conductivity is low, which means that it is difficult for a single-component sample to meet both high thermal conductivity and high strength. The copper-chromium-niobium series materials printed by gradient printing in this application can integrate the advantages of multiple alloys and have certain strength while having high thermal conductivity.
[0044] The above description is only an optional embodiment of the present application, and does not limit the patent scope of the present application. All equivalent structural transformations made by using the contents of the present application specification and drawings under the inventive concept of the present application, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present application.
Claims
1. A method for preparing copper-chromium-niobium series materials based on SLM, characterized in that: The following steps are involved: S1. Pre-treating a plurality of copper-chromium-niobium alloy powders respectively to obtain pre-treated copper-chromium-niobium series alloy powders; S2. Establish a three-dimensional solid model of the sample to be formed and import it into the SLM printer, set the printing parameters, respectively load the pre-treated copper-chromium-niobium series alloy powder into each powder bin of the SLM printer, evacuate and introduce protective gas, and then print the first copper-chromium-niobium material layer by layer until the nth layer; S3, replacing the powder bin, and printing the second copper-chromium-niobium material layer by layer starting from the n+1 layer according to the printing parameters to the required thickness; S4, repeat step S3 until the printing of various copper, chromium and niobium materials is completed to obtain a molded sample; The contents of Cr and Nb in each of the copper-chromium-niobium materials are different.
2. The method for preparing copper-chromium-niobium series materials based on SLM according to claim 1, characterized in that: The copper-chromium-niobium alloy powders include the following components by mass percentage: Cr: 0.8%-7%, Nb: 0.35%-4%, Fe≤0.005%, O≤0.05%, Si≤0.05%, Al≤0.05%, and the balance is Cu.
3. The method for preparing copper-chromium-niobium series materials based on SLM according to claim 2, characterized in that: In the various copper-chromium-niobium alloy powders, the mass ratio of Cr to Nb is 1.14:
1.
4. The method for preparing copper-chromium-niobium series materials based on SLM according to claim 3, characterized in that: In the step S3 and the step S4, each time the next copper-chromium-niobium material is printed, the content of Cr and Nb in the replaced powder bin increases gradually.
5. The method for preparing copper-chromium-niobium series materials based on SLM according to claim 1, characterized in that: The step of pre-treating the various copper-chromium-niobium alloy powders to obtain pre-treated copper-chromium-niobium alloy powders comprises: A variety of copper-chromium-niobium alloy powders were vacuum dried, cooled in the furnace, and then subjected to ultrasonic vibration treatment. After sieving through a 270-mesh sieve, the sieved material was taken to obtain pre-treated copper-chromium-niobium series alloy powders.
6. The method for preparing copper-chromium-niobium series materials based on SLM according to claim 5, characterized in that: In the step of vacuum drying, the drying temperature is 100°C-120°C, the drying time is 4h-10h, and the vacuum degree is 1×10 - 4 Pa-1×10 -3 Pa.
7. The method for preparing copper-chromium-niobium series materials based on SLM according to claim 5, characterized in that: In the step of performing ultrasonic vibration treatment, the ultrasonic vibration frequency is 35kHz-40kHz, the ultrasonic vibration deviation angle is 8°-10°, and the ultrasonic vibration treatment time is 5min-10min.
8. The method for preparing copper-chromium-niobium series materials based on SLM according to claim 1, characterized in that: The printing parameters include: The scanning speed is 400mm / s-1600mm / s, the scanning spacing is 0.05mm-0.12mm, the printing power is 370W-460W, and the printing single layer thickness is 0.02mm-0.08mm.
9. The method for preparing copper-chromium-niobium series materials based on SLM according to claim 1, characterized in that: In the step of evacuating the vacuum and introducing the protective gas, the vacuum is evacuated to a vacuum degree of 3Pa-5Pa, and the protective gas is argon.
10. The method for preparing copper-chromium-niobium series materials based on SLM according to claim 1, characterized in that: After step S4, the method further includes: Performing surface treatment on the molded sample to reduce surface roughness; The surface treatment method includes one or more of liquid sandblasting, abrasive flow machining, electrolytic polishing and chemical reagent cleaning.
Citation Information
Patent Citations
Copper alloy powder for additive manufacturing and preparation method and application of copper alloy powder
CN109794602A
Preparation method for batch type laser cladding production of CuCr composite contacts
CN111636061A
A method to improve the strength and electrical conductivity of Cu-Cr-Nb alloys
CN112317755B
Process method for preparing high-strength and high-conductivity copper-chromium alloy through SLM technology
CN118268591A
Method for preparing CuCrNb-316L bimetal integrated liquid rocket combustion chamber through SLM
CN118385606A
Cited By
Method for preparing copper-chromium-niobium alloy high-thermal-conductivity component based on green laser SLM
CN120190361A
Method for preparing spacecraft part based on 3D printing, spacecraft part and application
CN122517641A
